Nanotechnology-Based Strategies for Combating Emerging and Re-emerging Fungal Infections - Farnoush Asghari-Paskiabi1*; Zahra Jahanshiri1 (Journal of Medical Microbiology and Infectious Diseases)
The emergence and re-emergence of pathogenic fungi pose a significant challenge, fueled by factors like increased immunosuppression and climate changes. Despite the development of new antifungal drugs and therapies, controlling these infections remains a pressing issue. Candida auris, a multidrug-resistant yeast, has caused invasive infections with high mortality rates in hospitals worldwide, with Iran experiencing a particularly high burden of invasive C. auris infections. The identification of new at-risk groups, rising prevalence of resistant infections, and the emergence of novel multidrug-resistant pathogenic fungi highlight the need for novel therapeutic approaches and effective prevention strategies. This review explores the potential of nanotechnology, an emerging field, in combating emerging fungal infections, such as C. auris, and re-emerging infections caused by Fusarium and Rhizopus species. We conducted a literature review of studies exploring nanotechnology-based approaches to control or inhibit these emerging and re-emerging fungal pathogens with a particular focus on Iran and globally, where antimicrobial resistance is a growing concern. Nanotechnology revolutionizes antifungal strategies with novel solutions. Nanoparticles (NPs) and nanomaterials possess unique properties, such as enhanced solubility, targeted delivery, and ROS generation, which can disrupt fungal cell membranes, inhibit biofilm formation, and prevent sporulation. Their tailored sizes, high surface-to-volume ratios, and customizable surface chemistries make them game-changing solutions to combat drug-resistant fungal infections and improve treatment outcomes. Numerous studies have demonstrated the ability of various NPs, including silver, metal oxide, and carbon-based nanomaterials, to inhibit the growth and virulence factors of C. auris, Fusarium, and Rhizopus species. These nanomaterials exhibit potent antifungal activities through mechanisms such as disrupting cell membrane integrity, inducing oxidative stress, and inhibiting fungal metabolic pathways.